PWM Precision Flight Controller Cooling System for UAV in Pineapple Plantation - Magentharan, Shri Ganesh; Faizan, Omar Mohd; Halim, Nuruddin (Progress in Aerospace and Aviation Technology, 2023)
The use of a proper pulse width modulation (PWM) signal to maintain the cooling system and protect against excessive usage may be beneficial in reducing mechanical damage and extending flight endurance. The goal of this research is to create a cooling system that reduces thermal heat to extend the flying time of a UAV. The experiment was conducted in a confined environment with a room temperature of 32ºC. A PWM signal was used to develop and operate the proposed cooling system prototype and fan revolution speed and temperature were recorded every 15 seconds for 1 minute. Thermal heat is reduced by 6ºC from the baseline (40ºC), and the fan speed remains constant at 3000-3500 rpm during PWM 25% for 45-60 seconds. Thermal heat is reduced by 10ºC from the baseline, while the fan speed remains constant at 4000-5000 rpm for 45-60 seconds under PWM (75%-100%). The linearity of the PWM duty cycle and fan speed is 98%. However, the suitable duty cycle of PWM is set at 50%, and the temperature begins to fall below 30ºC after 45 seconds, indicating a favorable outlook for cooling systems. As a result, during PWM at 75% and 100% for 15 seconds, the operating signal is overused. The primary idea behind this project is to activate the DC motor fan when the temperature reaches 40ºC.